Impact of cable bacteria on sedimentary iron and manganese dynamics in a seasonally-hypoxic marine basin. (1st November 2016) - Sulu-Gambari, Fatimah; Seitaj, Dorina; Behrends, Thilo; Banerjee, Dipanjan; Meysman, Filip J.R.; Slomp, Caroline P.
Abstract: Cable bacteria have recently been identified in various sedimentary marine settings worldwide. These filamentous microbes mediate electrogenic sulphur oxidation (e-SOx) over centimetre-scale distances, leading to a distinct separation of oxygen- and sulphide-bearing sediment zones. Here we present results of a year-long monthly assessment of the impact of cable bacteria on sedimentary Fe and Mn dynamics at three sites located along a water depth gradient in a seasonally-hypoxic coastal marine lake (Grevelingen, The Netherlands). Fluorescence In Situ Hybridisation (FISH) shows the presence of cable bacteria at two sites in spring. Micro-sensor profiling (O2, pH, H2 S) and pore water profiles of dissolved Mn, Fe 2+, Ca 2+ and SO4 2− reveal the geochemical signature of e-SOx at these sites, i.e. the development of a broad suboxic zone, characterised by a low pH and acidic dissolution of Ca/Mn carbonates and Fe sulphides. Cable bacteria activity, as reflected by dissolution of FeS in spring, was highest at the deepest and most hypoxic site. In spring, dissolved Mn and Fe 2+ released at depth due to e-SOx diffused upwards and was sequestered as Mn- and Fe-(oxyhydr)oxides near the sediment surface, with Mn oxides acting as an oxidant for part of the upward diffusing Fe 2+ . Strikingly, the thickness of the Fe-(oxyhydr)oxide-bearing surface layer of the sediment was greatest at the most hypoxic site, emphasising the key role of cable bacteria in creating oxidised surface sediments. X-ray absorption fine structure analyses confirm the seasonality in Fe-(oxyhydr)oxide formation and reveal that the sediment Mn oxides were of biogenic (birnessite) and abiotic (hausmannite) origin. Upon the onset of hypoxia in early summer, the sediment Fe-(oxyhydr)oxides were mostly converted to Fe-sulphides but the Mn oxides dissolved and the Mn was lost to the overlying water. After summer hypoxia, Beggiatoaceae mats colonised the sediment with little further change in sediment geochemistry. Our results confirm that cable bacteria act as a key control on the coupled cycling of Fe and Mn in surface sediments of seasonally hypoxic basins.